Effect of interface contact conditions on adaptive finite element simulation of sheet forming operations - Ahmed, Mohd; Singh, Devender; Islam, Saiful (European Journal of Computational Mechanics, 2015)
Interfacial contact can have significant influence on adaptive mesh refinement during finite element simulation of sheet forming process. In this work, effect of contact is examined on the adaptive simulation of deep drawing operations having different friction factor and thickness of sheets. The frictional contact at the die-blank interface in the sheet of various thicknesses is modelled in terms of a constant factor relating frictional stress to shear strength of the material. An h-adaptive technique has been employed for the refinement of mesh. A recovery-type error estimator based on the energy norm is used for guiding the h-refinement. Adaptively refined meshes obtained during simulation of the axisymmetric deep drawing operation using frictional and non-friction contact on different sheet thicknesses are presented and discussed.